(untitled) (Universal International Scientific Journal, 2026)
This article aims to conduct scientific research on the pedagogical foundations of providing students of natural sciences with systematized, integrated knowledge based on the interconnection of physics, chemistry, and biology. This article is based on the results of an analysis of the literature on the topic of our research work and is devoted to the role and place of interdisciplinary interconnection in the history of education.